A method of forming a set of diagnostic features for optimizing control parameters and diagnosing technical systems - Hryhorenko, Ihor; Olkhovikov, Dmytro; Piskun, Serhii (Deutsche internationale Zeitschrift für zeitgenössische Wissenschaft, 2023)
It is substantiated that the control of the state of technical systems is aimed at increasing the reliability of information about the real technical state. An analysis of existing methods of substantiating sets of control parameters of complex technical systems is carried out, their disadvantages and advantages are given. The purpose of the study is to develop a method that allows you to justify the number of control parameters when determining the state of technical systems. The work proposes a method (order) of forming a set of diagnostic features for optimizing control parameters and diagnosing technical systems for assessing their technical condition, which consists of three stages. The basis for the wide use of the proposed method is the hidden potential of multidimensional test signals reflecting a wide range of differences that can be deployed with respect to the generalized control parameter.
Keywords: diagnostics; reliability; control; method; optimization; test signal; technical condition